A STUDY ON TEACHING SPEAKING OF ENGLISH DESCRIPTIVE TEXTTO THE TENTH YEAR STUDENT OF SMA PGRI 1 KARANGMALANGSRAGEN IN 2009/2010 ACADEMIC YEAR - SUTARTO, VIVIN INDIARTI (2010)
In this research, the writer describes the implementation of teaching speaking of English descriptive text, problems faced by the teacher in teaching speaking of English descriptive text, and problem faced by the students in learning speaking of English descriptive text. This research uses descriptive qualitative study that uses observation, interview, and document. The subject of this research is the tenth year students of SMA PGRI 1 Karangmalang Sragen. The writer takes X A students as the subject on the study. The results of the research show that: a) the minor ways of English descriptive text applied by teacher are: context exploration, text exploration based on model texts, joint construction of a text, and individual application, b) the material of teaching speaking of English descriptive text is suitable with syllabus and the teacher teaches the students uses the textbooks and the worksheet, c) the teaching speaking of English descriptive text are: the teacher uses four methods like context exploration, text exploration based on model texts, joint construction of a text, and individual application in order to cover the rule of KTSP 2006 and suitable with Genre-based Approach, d) the activities in classroom used by teacher are: role playing and discussion, e) classroom technique teaching speaking used by teacher are: the roles of the teacher and the students, group work, and guessing, f) the problems faced by the teacher in teaching speaking of English descriptive text are: limited time, classroom management, and the students capability, g) the problems faced by the students in learning speaking of English descriptive text are: limited vocabulary, pronunciation, and gramma